The social functional outcome of being naturalistically treated with paliperidone extended-release in patients with schizophrenia - Nakagawa R (Neuropsychiatric Disease and Treatment, 2015)
Ryoko Nakagawa,1 Takashi Ohnishi,1 Hisanori Kobayashi,1 Akihide Wakamatsu,2 Ai Tanimura,3 Kazuo Morita,3 Toshio Yamaoka,3 Hideo Usui,3 Yoshimasa Ogawa,3 Akiko Fujino,3 Kazutake Yoshizawa11Evidence Generation Department, Medical Affairs Division, 2Medical Affairs Strategy Department, Medical Affairs Division, 3Drug Safety Surveillance Department, Japan Safety and Surveillance Division, Janssen Pharmaceutical K.K., Tokyo, JapanBackground: Social functioning is an important outcome for patients with schizophrenia. To evaluate the effects of paliperidone extended-release (PAL-ER) on social function, symptomatology, and safety in the routine clinical practice, we conducted a 1-year post-marketing surveillance study of PAL-ER. We also explored relationships between symptomatic improvement and socially functional outcome in patients with schizophrenia.Patients and methods: Patients with an established diagnosis of schizophrenia were allowed flexible 3–12 mg/day dosing during the surveillance. Patients were assessed on social functioning using the Social and Occupational Functioning Assessment Scale (SOFAS) and on symptomatology using the Clinical Global Impression–Schizophrenia scale. All adverse events (AEs) were also collected.Results: A total of 1,429 patients were enrolled in the surveillance study, of whom 1,405 were evaluable for safety and 1,142 were evaluable for efficacy. The treatment discontinuation rate for any reason during the observation period was 34.66%. Significant improvements were observed on both Social and Occupational Functioning Assessment Scale and Clinical Global Impression–Schizophrenia scale during the observation period. The percentage of patients with socially functional remission (SOFAS ≥61) also increased significantly. A significant association between early improvements in positive symptoms, sex, severity of negative symptoms at baseline, and socially functional remission was observed. A total of 33.52% of patients had AEs and 8.75% of patients had serious AEs. Despite the recommendation of monotherapy with PAL-ER, 65.84% of patients were given additional antipsychotics (polypharmacy). Post hoc comparisons of monotherapy versus polypharmacy revealed that the monotherapy group had better outcomes and fewer AEs than the polypharmacy treated group. The improvement in social functioning and the rate of socially functional remission did not differ between groups.Conclusion: PAL-ER treatment showed effective symptom control and improvement in social functioning. The data suggest that early response to antipsychotic treatment should be important for functional outcomes.Keywords: paliperidone, social function, schizophrenia, naturalistic study